Overview of malaria prevention and treatment management in The Gambia: a descriptive study - Jassey, Babucarr; Manjang, Buba; Camara, Jerreh; Jallow, Adama HO; Marong, Lamin; Jawneh, Sedia S; Sarr, Pa Ousman; Drammeh, Alagie Lamin; Ndow, Ousman; Tabally, Omar T; Jeng, Modou Lamin; Mbye, Aji Fatou; Conteh, Bubacarr; Jammeh, Ramatoulie; Drammeh, Abubacarr (JHeS (Journal of Health Studies), 2023)
Malaria is a significant public health problem in The Gambia, a country in West Africa with a population of about 2.4 million people. The disease is endemic in the country and is a major cause of morbidity and mortality, especially among children under five. Malaria prevention strategies are essential in The Gambia. Although not totally but significantly, several techniques have been implemented in The Gambia to combat the spread of malaria to prevent and control the disease. This study aims to explore and provide an overview of strategies implemented in The Gambia to prevent and manage malaria in children under five. The study was a descriptive study using situational analysis with an extension of the basic guidelines established by WHO to prevent malaria by analyzing the latest developments on the progress made in The Gambia. The Gambia has made significant progress in preventing and controlling malaria through strategies, including insecticide-treated nets (ITNs), indoor residual spraying (IRS), antimalarial treatment, education and awareness, and environmental management. Sustained efforts and investments in these strategies are critical to reducing the population burden of malaria and achieving the goal of malaria elimination.